Thrombolysis versus unfractionated heparin for hemodynamically stable patients with pulmonary embolism: a systematic review and meta-analysis - N. A. Cherepanova; A. А. Podlipaeva; E. S. Andreeva; E. N. Umyarova; I. S. Mullova; T. V. Pavlova; D. V. Duplyakov (Российский кардиологический журнал)
Currently, thrombolytic therapy (TLT) for pulmonary embolism (PE) is recommended only for patients with high-risk PE. At the same time, in real practice, TLT is often performed in hemodynamically stable patients. The main contradiction arises due to the different risk-benefit ratio of TLT in comparison with anticoagulant monotherapy.Aim. To assess the benefits of TLT, compared with unfractionated heparin (UFH) monotherapy, in hemodynamically stable patients with PE in reducing mortality, recurrence of PE and risk of bleeding.Material and methods. Randomized controlled trials were searched in PubMed, Embase, and Cochrane Library databases. Of the 3050 publications found, 100 papers were selected for a detailed study. As a result of detailed analysis, 7 randomized clinical trials (n=1611) remained according to established criteria.Results. TLT in hemodynamically stable patients with PE, in comparison with UFH, showed a tendency to decrease in the inhospital death rate: 2,39% vs 3,68 (odds ratio (OR): 0,73; 95% confidence interval (СI): 0,34-1,57), and a decrease in the composite endpoint (death and/or recurrent PE): 3,14% vs 5,15% (OR: 0,61; CI: 0,37-1,01). There was a significant increase in the number of major bleeding: 8,81% vs 2,70% (OR: 3,35; 95% CI: 2,06-5,45). TLT in hemodynamically stable patients with PE to a greater extent can reduce the pulmonary blood pressure, perfusion defects according to lung scintigraphy, as well as the need for therapy intensification. However, the heterogeneity of studies and the small number of participants require caution when interpreting their results.Conclusion. TLT in patients with PE and stable hemodynamics tends to reduce mortality and/or recurrence of PE, but increases the incidence of major bleeding. Further studies need to determine the phenotypes of hemodynamically stable patients with PE who would benefit from TLT.